ديناميكية التغير في التركيب الكيميائي لبذور الفول العادي تحت تأثير التغذية البوتاسية وموعد الحصاد (Latakia University Journal -Biological Sciences Series, 2019)
نفذ البحث في أثناء الموسمين الزراعيين 2005 – 2006 لدراسة تأثير خمسة معدلات من التغذية البوتاسية 0، 20، 40، 60، 80 كغ K2O  / هـ وثلاثة مواعيد للحصاد عند نضج 50، 75،  100% والتداخل بين هذه العوامل على ديناميكية التغير في التركيب الكيميائي للبذور بينت الدراســة مايلي: • سـببت التغذية البوتاســية المتزايدة زيادة معنوية في نســبة الرطوبة، والبروتين والزيت، واللب والآزوت والبوتاس في البذور.في حين كانت الزيادة غير معنوية في نســبة الألياف والفوسفور مقارنةً بالشاهد.• أعطى موعد الحصاد عند نسبة نضج 100% زيادة معنوية في نسـبة البروتين والآزوت  والبوتاسيوم فقط، بالمقابل انخفضت نسبة الزيت واللب والألياف والفوســـفور.• أظهر التداخل بين عوامل التجربة تأثيراً معنوياً في نسبة الرطوبة، والبروتيــن واللـب والآزوت في البذور في حين كان التأثير غير معنوي في نسبة الزيت والألياف والفوسفور. The research was carried out during 2005 – 2006 to study the effect of 5 rates from potassium nutrition that, 0, 20, 40, 60, 80 Kg K2O / ha-1 3  with three dates of harvesting at 50 %, 75 %, 100 %, focusing on the interaction among these factors on dynamics of changing chemical composition of the seeds of faba bean. Results revealed the following: • Increased rates of potassium nutrition caused significant increase in the percentage of moisture, protein, oil, kernels, N and K in seeds compared with the control; but there were not significantly increases in fiber percentage and P. • The date of harvesting at maturity percentage 100 % led to a significant increase just in the percentage of protein and nitrogen. On the other hand, the percentage of oil, kernels, fiber, and P decreased. • The interaction among experiment factors significantly increases moisture, protein, kernels, and N. But there was not significant effect in the percentage of oil, fiber, and P.